2021
DOI: 10.3389/fpubh.2021.704577
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Stress and Coping During the COVID-19 Pandemic in Families With and Without Children With Developmental Disorders or Chronic Conditions

Abstract: Objectives: To compare COVID-19-induced stress and coping in families with and without children diagnosed with developmental disorders or chronic conditions.Methods: In this mixed-method design study, an online survey collected information on parental stress levels before and during COVID-19, sources of stress, and coping strategies using open-ended questions. Qualitative answers were categorized thematically. Multiple linear regression models were built for the association between changes in stress levels (du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…During the current study, most participants experienced a period of remote learning (from 4 to 7 months). Remote learning was characterized by an increased proportion of independent tasks, a decreased number of topics, and a great variety of interaction opportunities, and it was evaluated by parents in Latvia as a significant source of stress ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the current study, most participants experienced a period of remote learning (from 4 to 7 months). Remote learning was characterized by an increased proportion of independent tasks, a decreased number of topics, and a great variety of interaction opportunities, and it was evaluated by parents in Latvia as a significant source of stress ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…In children with lung diseases -who are therefore more vulnerable to COVID-19-one study found more anxiety in children and parents than in healthy controls [13], whereas another study could only confirm this result in mothers, as they showed that healthy children experienced more anxiety [14]. Studies that compared children with CSC in general to healthy controls also found conflicting results [15][16][17]. Moreover, little is known about changes in daily life activities due to COVID-19 in children with CSC.…”
Section: Introductionmentioning
confidence: 99%
“…This is paired with high uncertainty regarding how the pandemic will evolve and how it will affect individuals. School and day care closures and job insecurities put additional strain on families (Martinsone & Tzivian, 2021). Accordingly, early meta-analyses suggest high levels of COVID-19-related psychological stress (Cooke, Eirich, Racine, & Madigan, 2020).…”
Section: Introductionmentioning
confidence: 99%